Price Discrimination with Demarketing1. (21st February 2017) - Kim, Jaesoo; Shin, Dongsoo
Abstract : We study how demarketing interacts with pricing decisions to explain why and when it can be employed as the seller's optimal strategy. In our model, a monopolistic seller offers different price‐quality bundles of the product. A consumer's preference is private information. With demarketing, consumers must make a costly effort to purchase and/or utilize the product, whereas with marketing, the seller instead makes the effort so that the consumer's purchasing decision is independent of the cost of effort. Our result suggests that, for small or large effort costs, it is optimal for the seller to engage in marketing. For intermediate effort costs, however, demarketing can be optimal. With demarketing, the seller induces only the consumers with high valuation to make transaction effort. By doing so, the seller can price discriminate more effectively, thus extracting more surplus. We extend our analysis to the case where the seller can offer special deals through exclusive sales channels along with demarketing. Then, demarketing can be optimal even for large costs of effort.